Concepts of Transformational Leadership, Self-efficacy, and Employee Engagement on Employee Performance - Wenny Desty Febrian; Romadina Permatasari; Indra Sani (International Journal of Global Sustainable Research, 2023)
The purpose of this study is to review previous articles, looking for relationships between variables. This study is a literature review, does not involve data processing, and does not have a research sample. The conclusion of this study is that there is a relationship between the variables observed in previous research, which supports the review of the literature in this article. What is new in this article is that no one has taken into account all the independent variables of the addict. The number of important articles allows the article to become a reference for further research and quantitative developments.